Complete mitochondrial genome of Acropteris iphiata (Lepidoptera: Uraniidae). Issue 2 (3rd July 2019) - Sanaei, Ehsan; Park, Jeong Sun; Jeong, Jun Seong; Kim, Min Jee; Kim, Iksoo
Abstract: Acropteris iphiata belongs to the family Uraniidae in the superfamily Geometroidea (Lepidoptera). We sequenced 15, 346-bp long complete mitochondrial genome (mitogenome) of the species, which consists of a typical set of genes (13 protein-coding genes, 2 rRNA genes, and 22 tRNA genes) and one major non-coding A + T-rich region. The A. iphiata mitogenome harbored the gene order tRNA Met, tRNA Ile, and tRNA Gln between the A + T-rich region and ND2 that is found in most lepidopteran mitogenomes. Bayesian inference (BI) and maximum likelihood (ML) phylogeny, using 13 protein-coding genes (PCGs) and 2 rRNAs showed that A. iphiata was placed as a sister to Geometridae with the highest nodal support (Bayesian posterior probabilities for BI = 1.00 and Bootstrap support for ML = 100).